IN CULTIVATION MULBERRY SEEDLINGS SCIENTIFIC WITH NEW METHODS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The article discusses the issue of increasing the forage base of the silkworm using modern methods, which is currently a serious problem in the sericulture industry.